2013
DOI: 10.1037/a0029007
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and anxiety mediate the effect of loneliness on depressed mood and sleep quality in college students.

Abstract: This study helps explain how loneliness dynamics relate to poor health and suggests specific points of departure for the development of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
2
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 52 publications
12
143
2
12
Order By: Relevance
“…Namely, and replicating prior work (e.g. Nolen-Hoeksema & Morrow, 1991;Sontag & Graber, 2010;Verkuil et al, 2012;Zawadzki et al, 2013), greater perceived stress or stressful situations predict greater rumination. In turn, engaging in rumination can create and extend stress responding (e.g.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Namely, and replicating prior work (e.g. Nolen-Hoeksema & Morrow, 1991;Sontag & Graber, 2010;Verkuil et al, 2012;Zawadzki et al, 2013), greater perceived stress or stressful situations predict greater rumination. In turn, engaging in rumination can create and extend stress responding (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…Research has found that individuals engage in more rumination when they experience stress (Nolen-Hoeksema & Morrow, 1991;Sontag & Graber, 2010;Verkuil, Brosschot, Meerman, & Thayer, 2012;Zawadzki, Graham, & Gerin, 2013). When individuals ruminate they experience more negative emotional states (e.g.…”
Section: Why Would Rumination Be So Deleterious?mentioning
confidence: 99%
See 2 more Smart Citations
“…Ruminative and anxiety-producing thought patterns over time are associated with increased levels of depression and poor sleep quality (Irwin et al, 2006;Zawadzki, Graham et al, 2013a). Thus, people who do SSLAs that distract them from their negative thoughts would likely have better health outcomes, such has been found among cancer patients (Folkman & Moskowitz, 2004;Kennedy & LloydWilliams, 2009).…”
Section: Avoiding Negative Thoughtsmentioning
confidence: 99%